Drugs in R&D - van Rensburg, Anton; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Adis.)
Drugs in R&D is an international, peer reviewed, open access, online only journal, and provides timely information from all phases of drug research and development that will inform clinical practice. Healthcare decision makers are thus provided with knowledge about the developing place of a drug in therapy. The Journal includes: Preclinical (in vitro and in vivo) research of direct relevance to clinical drug development Negative/neutral study data Studies on discontinued drugs/indications Drug stability studies Bioequivalence and biosimilar studies .
Keywords: Therapeutics; Pharmacology; Internal medicine; Therapeutics; Pharmacology; Internal Medicine